ACADEMIC INTEGRITY AS A COMPONENT OF THE QUALITY ASSURANCE SYSTEM OF HIGHER EDUCATION - Iliichuk, Liubomyra (Mountain School of Ukrainian Carpaty, 2021)
The article emphasizes that the formation of a culture of academic integrity in the higher education system of Ukraine is one of the key tasks of the state educational policy, the solution of which directly depends on increasing confidence in Ukrainian academic science and improving the quality of higher education in our country. It is emphasized that the issues of implementation of academic integrity to international practices, as well as the creation and implementation of a comprehensive strategy for the formation of a culture of academic integrity of higher education and the educational community at the state level and within the free economic activities. It is noted that this problem has recently been the subject of scientific research and discussions on various academic platforms, which aim to outline the most effective ways to implement and adhere to the principles of academic integrity in higher education, which directly reflects the level of culture and social values education in Ukraine, the formation of a system of values of future professionals. It is noted that the practice of implementing academic integrity has been widely used in Europe and the United States and is enshrined in law for its implementation and observance in higher education institutions of Ukraine. Emphasis is placed on the fact that in accordance with the current norms of educational legislation, higher education institutions have the right to independently develop a policy of academic integrity and take appropriate measures to implement it in the educational environment of free educational institutions. The policy and mechanisms of formation of high culture of quality of education and academic integrity in Vasyl Stefanyk Precarpathian National University are outlined.